Effectiveness of structured continuing professional development program on nurse job satisfaction and competence: quasi-experimental study - Ria Desita Natalia; Regina V. T Novita; Sudibyo Supardi (LPPM Politeknik Sandi Karsa, South Sulawesi, Indonesia, 2026)
Introduction: Continuing Professional Development (CPD) is considered a strategic approach to strengthening nurses' competence and improving job satisfaction. However, evidence regarding structured CPD programs grounded in nursing theory remains limited, particularly in Indonesian hospital settings. This study aimed to evaluate the effectiveness of a structured CPD program based on patricia benner's framework from novice to expert in improving nurses' job satisfaction and professional competence. Research Methodology: A quasi-experimental pretest-posttest control-group design was employed with 92 clinical nurses (46 in the intervention group and 46 in the control group), selected using purposive and cluster sampling. The intervention consisted of a two-month structured CPD program integrating face-to-face learning, e-learning, and clinical mentoring. Job satisfaction was measured using a validated job satisfaction questionnaire, while competence was assessed using the Nurse Competence Scale (NCS). Data were analyzed using the Wilcoxon signed-rank test, Chi-square test, Mann-Whitney U test, and binary logistic regression analyses. Results: The intervention group demonstrated significant improvements in job satisfaction (10.7%; p=0.010) and nurse competence (7.4%; p<0.001). Multivariate analysis identified participation in the structured CPD program as the strongest predictor of improved job satisfaction (OR=2.64, 95% CI: 1.03–6.80; p=0.042) and competence (OR=6.88, 95% CI: 1.94–24.38; p=0.003), after controlling for nurses' working period. The control group showed no statistically significant improvement in either outcome. Conclusion: A structured CPD program based on Patricia Benner's competency framework effectively enhanced nurses' job satisfaction and professional competence. Hospitals should integrate structured, competency-based CPD into routine workforce development strategies to strengthen nursing performance and improve the quality of healthcare services.